2016
DOI: 10.1111/eth.12516
|View full text |Cite
|
Sign up to set email alerts
|

Personality in Blue Tits (Cyanistes caeruleus) and its Effect on Their Breeding Success

Abstract: In this study, we investigated whether blue tits (Cyanistes caeruleus) showed 22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 14 ). Indeed, personalities have now been associated with key elements of evolutionary fitness such as survival 9 and reproductive success 5 , 21 . Furthermore, individuals with different personality types have been shown to play different ecological roles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“… 14 ). Indeed, personalities have now been associated with key elements of evolutionary fitness such as survival 9 and reproductive success 5 , 21 . Furthermore, individuals with different personality types have been shown to play different ecological roles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in avian evolutionary ecology aim to identify factors associated with variation in reproductive success, whereby reproductive success is often treated as a continuous variable, for example measured as the number of offspring that fledge or the proportion of hatchlings that fledge (Mutzel et al., , Colchester & Harrison, ; Pollock et al., ). However, our results show that complete brood failure and partial brood loss are typically caused by different processes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report on a 7-year study of blue tits (Cyanistes caeruleus) in which we used a uniquely comprehensive dataset on parental nestbox visits to investigate the association between parental behaviour and nestling mortality. The blue tit and its close relative the great tit (Parus major) have served as model species in evolutionary ecology and many studies have identified factors that are associated with variation in nestling survival until fledging, such as the degree of urbanization (Chamberlain et al, 2009;Pollock, Capilla-Lasheras, McGill, Helm, & Dominoni, 2017), timing of reproduction (Reed, Jenouvrier, & Visser, 2013;Verhulst & Nilsson, 2008), habitat characteristics (Lambrechts et al, 2004;Tremblay, Thomas, Lambrechts, Blondel, & Perret, 2003) and personality traits (Colchester & Harrison, 2016;Mutzel, Dingemanse, Araya-Ajoy, & Kempenaers, 2013). However, even in these intensively studied species, little is known about the proximate causes underlying mortality during the nestling period at individual nests.…”
mentioning
confidence: 99%
“…Also, the successful urban colonizer must adopt or express substantial behavioral plasticity to different habitat structures and the density of the human population in towns [5,8,9]. Although many studies have analyzed the urbanization process, much less is understood about how animal populations differ in habitat requirements between urban and rural areas and how this difference mediates the behavior of animals [8,[10][11][12][13][14]. The selection of sites by animals to meet their requirements is a behavioral process itself; however, it is more related to physical components of the environment rather than any other types of behavior linked with the presence of conspecifics or different species (e.g., aggressive behavior or flocking).…”
Section: Introductionmentioning
confidence: 99%